Can the Discreditable be an Advantage? Mental Illnesses as Metaphors on Rhetorical Usages for Language Teaching - Shih, Yu-Chun; Chen, Shu-Chuan (Master Program in Linguistics, Diponegoro University, 2019)
Mental illnesses often inspire artists and writers and are omnipresent in various works, yet the moral adequacy of portraying their images remained controversial: Erving Goffman (2010) had described the challenges the â€œdiscreditablesâ€ might have faced and the privileges they might get once being uncovered in his essay. However, Susan Sontag believed that wrapping disease in metaphors discouraged, silenced, and shamed patients in her Illness as Metaphor. This paper aims to center the discussion on what the diseases and the patients will represent and the privileges be demonstrated in these texts from a rhetorical aspect? By applying principally the theories of uncanny, abjection, and stigma, this paper has built a theory on presuming Meursault in Camusâ€™s The Stranger has Asperger, then analyze the power of stigma in two recent works: the episode â€œADHD Is Necessaryâ€ in Taiwanese TV drama: On Children, and a French novel: Nothing Holds Back the Night. The results showed that the mental illness can be an advantageous and necessary metaphor, just as an endowing â€œMark of Cainâ€, threatening yet defensive. Meanwhile